γ-Secretase Modulatory Proteins: The Guiding Hand Behind the Running Scissors - Wong, Eitan; Frost, Georgia R.; Li, Yue-Ming (Frontiers in Aging Neuroscience, 2020)
Described as the “proteasome of the membrane” or the “scissors in the membrane”, γ-secretase has notoriously complicated biology and even after decades of research, the full extent of its regulatory mechanism remains unclear. γ-Secretase is an intramembrane aspartyl protease complex composed of four obligatory subunits: Nicastrin (NCT), Presenilin (PS), Presenilin Enhancer-2 (Pen-2), and Anterior pharynx-defective-1 (Aph-1). γ-Secretase cleaves numerous type 1 transmembrane substrates, with no apparent homology, and plays major roles in broad biological pathways such as development, neurogenesis and cancer. Notch and the amyloid precursor protein (APP) and are undoubtedly the best studied γ-secretase substrates because of their role in cancer and Alzheimer’s disease (AD) and therefore became the focus of increasing studies as an attractive therapeutic target. The regulation of γ-secretase is intricate and involves the function of multiple cellular entities. Recently, γ-secretase modulatory proteins (GSMPs), which are non-essential subunits and yet modulate γ-secretase activity and specificity, have emerged as an important component in guiding γ-secretase. GSMPs are responsive to cellular and environmental changes and therefore, provide another layer of regulation of γ-secretase. This type of enzymatic regulation allows for a rapid and fine tuning of γ-secretase activity when appropriate signals appear enabling a temporal level of regulation. In this review we discuss the latest developments on GSMPs and implications on the development of effective therapeutics for γ-secretase-associated diseases such as AD and cancer.